Association of the variants CASP8 D302H and CASP10 V410I with breast and ovarian cancer risk in BRCA1 and BRCA2 mutation carriers - Engel, Christoph; Versmold, Beatrix; Wappenschmidt, Barbara; Simard, Jacques; Easton, Douglas F.; Peock, Susan; Cook, Margaret; Oliver, Clare; Frost, Debra; Mayes, Rebecca; Evans, D. Gareth; Eeles, Rosalind; et al. (Cancer epidemiology, biomarkers & prevention, 2010)
Background: The genes caspase-8 (CASP8) and caspase-10 (CASP10) functionally cooperate and play a key role in the initiation of apoptosis. Suppression of apoptosis is one of the major mechanisms underlying the origin and progression of cancer. Previous case-control studies have indicated that the polymorphisms CASP8 D302H and CASP10 V410I are associated with a reduced risk of breast cancer in the general population.Methods: To evaluate whether the CASP8 D302H (CASP10 V410I) polymorphisms modify breast or ovarian cancer risk in BRCA1 and BRCA2 mutation carriers, we analyzed 7,353 (7,227) subjects of white European origin provided by 19 (18) study groups that participate in the Consortium of Investigators of Modifiers of BRCA1/2 (CIMBA). A weighted cohort approach was used to estimate hazard ratios (HR) and 95% confidence intervals (95% CI).Results: The minor allele of CASP8 D302H was significantly associated with a reduced risk of breast cancer (per-allele HR, 0.85; 95% CI, 0.76-0.97; Ptrend = 0.011) and ovarian cancer (per-allele HR, 0.69; 95% CI, 0.53-0.89; Ptrend = 0.004) for BRCA1 but not for BRCA2 mutation carriers. The CASP10 V410I polymorphism was not associated with breast or ovarian cancer risk for BRCA1 or BRCA2 mutation carriers.Conclusions: CASP8 D302H decreases breast and ovarian cancer risk for BRCA1 mutation carriers but not for BRCA2 mutation carriers.Impact: The combined application of these and other recently identified genetic risk modifiers could in the future allow better individual risk calculation and could aid in the individualized counseling and decision making with respect to preventive options in BRCA1 mutation carriers.
Gesehen am 16.03.2023